Benzodiazepine Prescribing in Older Adults in U.S. Ambulatory Clinics and Emergency Departments (2001–10). Issue 10 (29th September 2015) - Marra, Erin M.; Mazer‐Amirshahi, Maryann; Brooks, Gillian; van den Anker, John; May, Larissa; Pines, Jesse M.
<x xml:space="preserve">Abstract</x> Objectives To assess trends in benzodiazepine use from 2001 to 2010 in older adults in U.S. ambulatory clinics and emergency departments (EDs). Design Retrospective analysis. Setting 2001 to 2010 National Ambulatory Medical Care Survey (NAMCS) and National Hospital Ambulatory Medical Care Survey (NHAMCS). Participants Individuals aged 65 and older for whom the reason for visit might prompt a physician to use a benzodiazepine (e.g., anxiety, detoxification, back sprain). Measurements The NAMCS and NHAMCS were used to evaluate U.S. ambulatory clinic and ED visits. Encounters involving individuals aged 65 and older for whom a benzodiazepine might be prescribed were analyzed. Trends in benzodiazepine use in these visits were explored, and predictors of use were assessed using survey‐weighted chi‐square tests and logistic regression. Results From 2001 to 2010, benzodiazepines were used in 16.6 million of 133.3 million ambulatory clinic visits and 1.9 million of 18.1 million ED visits with the selected reasons for the visits. There was no change in benzodiazepine use in either setting over the study period, although benzodiazepine use for those aged 85 and older increased from 8.9% to 19.3% in ambulatory clinics and 10.1% to 17.2% in EDs. Individuals visiting clinics with anxiety were five times as likely to receive benzodiazepines (odds ratio (OR) = 4.8), and those in EDs were twice as likely (OR = 2.3). Conclusion Despite safety concerns, benzodiazepine use in older adults in U.S. ambulatory clinics and EDs did not change from 2001 to 2010. In the oldest individuals, who are at higher risk of adverse events, a greater increase was seen than in those aged 65 to 84. Additional measures may be needed to promote alternatives to benzodiazepines.